2011
DOI: 10.3109/17435390.2011.587031
|View full text |Cite
|
Sign up to set email alerts
|

Improving the selective cancer killing ability of ZnO nanoparticles using Fe doping

Abstract: This work reports a new method to improve our recent demonstration of zinc oxide (ZnO) nanoparticles (NPs) selectively killing certain human cancer cells, achieved by incorporating Fe ions into the NPs. Thoroughly characterized cationic ZnO NPs (∼6 nm) doped with Fe ions (Zn(1-x )Fe (x) O, x = 0-0.15) were used in this work, applied at a concentration of 24 μg/ml. Cytotoxicity studies using flow cytometry on Jurkat leukemic cancer cells show cell viability drops from about 43% for undoped ZnO NPs to 15% for Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“…4,10,12,25 For the PI-flow cytometry method, four different ZnO NP concentrations of 0, 0.3, 0.6, and 0.9 mM were employed, and the cell viability was determined after 24 h of treatment. The cell viability data of Hut-78 cells determined using the PI-flow cytometry method, shown in Figure 6A, confirm our previously reported strong cytotoxicity of ZnO NP to cancerous cells.…”
Section: Experimental Results and Discussionmentioning
confidence: 99%
“…4,10,12,25 For the PI-flow cytometry method, four different ZnO NP concentrations of 0, 0.3, 0.6, and 0.9 mM were employed, and the cell viability was determined after 24 h of treatment. The cell viability data of Hut-78 cells determined using the PI-flow cytometry method, shown in Figure 6A, confirm our previously reported strong cytotoxicity of ZnO NP to cancerous cells.…”
Section: Experimental Results and Discussionmentioning
confidence: 99%
“…Several observations suggested that ZnO NPs may be employed as selective and smart cytotoxic agents for the eradication of cancer cells. In this regard, Aaron Thurber et al (2012) reported a new method to improve the selective anticancer effects of ZnO NPs using 7.5% Fe doping (Thurber et al 2012). Additionally, ZnO NPs exerted a cytotoxic effect on the human MCF-7 and glioma cell lines, while no cytotoxic effect was observed on normal human cell (Fakhroueian et al 2014;Ostrovsky et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…17 Furthermore, we determined that the nanoparticles caused their cytotoxic effect in OECM1 through mitochondria-mediated autophagy. 18 Similarly, Thurber et al 19 have demonstrated that Fe doping of ZnO nanoparticles improved their ability to selectively kill leukemia cells. They suggested that pure iron possesses potential as a cancerselective anticancer agent, in accordance with our results.…”
mentioning
confidence: 99%